1999
DOI: 10.1111/1468-5957.00251
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trading Methods on Volatility and Liquidity: Evidence from the Taiwan Stock Exchange

Abstract: This study contrasts the call and continuous auction methods using Taiwan Stock Exchange data. Volatility under the call market method is approximately one-half of that under the continuous auction method. The call market method is more effective in reducing the volatility of high-volume stocks than low-volume stocks. This contradicts conventional wisdom which suggests that the call market method is superior for thinly traded stocks, while the continuous auction method is preferred for heavily traded stocks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…One explanation could be that the creation of a continuous random order arrival sequence significantly increases price fluctuation. This finding is somewhat aligned with Chang et al (1999) who found lower volatility levels under the call auction system in Taiwan. However, the impact of trading arrangements on the relationship uniting volatility and efficiency remains to be investigated.…”
Section: Microstructures and Financial Reformssupporting
confidence: 83%
“…One explanation could be that the creation of a continuous random order arrival sequence significantly increases price fluctuation. This finding is somewhat aligned with Chang et al (1999) who found lower volatility levels under the call auction system in Taiwan. However, the impact of trading arrangements on the relationship uniting volatility and efficiency remains to be investigated.…”
Section: Microstructures and Financial Reformssupporting
confidence: 83%
“…Theissen (2000) reports that the CMM and CAM are more price efficient than dealer markets. Chang et al (1999) find that trading under the CMM is less volatile and more efficient than under the CAM.…”
Section: Relevant Literature and Motivation For The Studymentioning
confidence: 79%
“…A few exceptions include studies of the Tokyo Stock Exchange(Lehmann and Modest, 1994;Hamao and Hasbrouck, 1995; Ahn et al, 2002a,b), the Taiwan Stock Exchange(Chang et al, 1999), the Paris Bourse(Biais et al, 1995), and recently the Hong Kong Stock Exchange (e.g.,Ahn et al, 2001). 2 A secondary reason for studying the KLSE is that we can examine price limit performance within a periodic call market.…”
mentioning
confidence: 99%